Factor influencing of teachers’ readiness to implement the Independent Curriculum - Delita, Fitra; Sidauruk, Tumiar; Hanana, Alna; Wirda, Mona Adria (International Journal of Evaluation and Research in Education (IJERE), 2025)
The education curriculum in Indonesia is gradually changing from the 2013 Curriculum to the Independent “Merdeka” Curriculum. The new curriculum is certainly a challenge for teachers. The aim of this research is to analyze the factors that influence teacher’s readiness and to measure the level of teacher readiness in implementing the Independent Curriculum. This quantitative research was designed using a survey method. The participants involved were 172 teachers from elementary, middle, and high school education levels in Medan City, Indonesia. Data were collected using online questionnaires and interviews. Data analysis was conducted using descriptive statistics using mean scores, factor analysis, and multiple linear regression t-test. The research results show the level of teachers’ readiness in implementing the Independent Curriculum based on gender, age, and years of teaching experience, both at elementary, middle, and high school levels with a mean interval of 6.00–6.99 (the initiation level). Subsequently, there are four dominant factors that influence teachers’ readiness to implement the Independent Curriculum, which are teacher, school, government policy, and student. The teacher factor contributed the most in determining teachers’ readiness to implement the Independent Curriculum (43.7%).